Комары-лимонииды (Diptera, Limoniidae) из группы Ilisia (Parilisia) fausta (AL.) в фауне советской Средней Азии - Савченко, Е.Н. (Вестник зоологии, 1983)
Five maculate wing species of Ilisia(Parilisia) fausta-group from the Soviet Middle Asia are described as new: I. (P.) albibasis Sav. sp. n. (Zailiysky Ala-Tau and Alaisky mountain ranges), I. (P.) variegata Sav. sp. n. (Darwazsky and Pelra Pervogo mountain ranges), I. (P.) caudala Sav. sp. n. (Zailiysky Ala-Tau and Kungey Ala-Tau mountain ranges), I. (P.) serratofalcata Sav., sp. n. and I. (P.) obtusirama Sav. sp. n. (Darvazsky mountain range). From all known species of the «faustas-group and each from other they differ by the male hypopygium structure characters (Figs 2, 3). Type material is deposited in the collection of the 1. I. Schmalhausen Institute of Zoology (Kiev).